Paternalistic Leadership: A Hybrid Systematic Literature Review and Bibliometric Analysis - Fransisca Tuti Rahayu (EKONOMI DAN BISNIS DIGITAL, 2025)
This study aims to analyze the style of paternalistic leadership in the modern industrial context, particularly its impact on social change, organizational development, and innovation, using a Systematic Literature Review (SLR) and bibliometric analysis based on Scopus data (2008–May 9, 2025), visualized through VOSviewer. The analysis reveals that a well-balanced implementation of paternalistic leadership can serve as an effective strategy for sustainable organizational development, especially in cultures where this leadership style has been historically accepted. The findings are applicable across various sectors such as management, education, and business that require the adaptation of cultural values to foster innovation and social transformation. The novelty of this research lies in its integration of culturally rooted leadership values—such as the principle of Ing Ngarsa Sung Tuladha by Ki Hadjar Dewantara—to develop a modern leadership model that remains grounded in local cultural foundations.